The historian's Awakening : reading Kate Chopin's classic novel as social and cultural history - Chopin, Kate, 1850-1904 (Historian's annotated classics., 2019)
"The Historian's Awakening is a full commentary on the text (included) that provides social and cultural history context, discussions of the author and her times as well as valuable insight into historical forces that shaped people's lives"--